Legalitas Perkawinan Beda Agama dalam Sudut Pandang Undang-Undang Perkawinan dan Undang-Undang Administrasi Kependudukan Dikaitkan dengan Hak Asasi Manusia - Wiedhar Saputri, Ananda Megha; Sutarni, Nanik; Sholikah, Dwi Imroatus (Jurnal Bedah Hukum, 2023)
The background of this research is that interfaith marriages are not explicitly regulated in Law no. 16 of 2019 concerning Amendments to Law no. 1 of 1974 concerning Marriage, so there is a legal vacuum to strictly regulate interfaith marriages in Indonesia. This is because more and more people in Indonesia are doing interfaith marriages. With the Law no. 23 of 2006 concerning Population Administration (UU Adminduk) can accommodate interfaith marriages being disabled, but in practice it is best not to do so. Article 35 letter a of the Adminduk Law relating to interfaith marriages is a special rule that overrides more general regulations and does not erase old provisions, so that Law no. 16 of 2019 concerning Amendments to Law no. 1 of 1974 concerning Marriage is still valid in the national regulatory system in the field of marriage. With the existence of rules that prohibit interfaith marriages as a solution to overcome the legal vacuum by not giving rights to interfaith marriage actors to register their marriages through a court order. As for the legality of marriage materially, it still returns to the laws of their respective religions, while with regard to formal, civil law relations arising from marriage, if the marriage has received legal recognition, then everything is protected by law. The rejection of interfaith marriages in Indonesia is basically a discriminatory act that is not in accordance with the principles of Human Rights (HAM) itself. However, humans are obliged to prioritize their basic human obligation to comply with their religious laws and the state as law enforcer needs to regulate prohibitions on interfaith marriages so that violations do not occur in society.